An assessment model for temporary multi-organisational (TMO) integration in construction projects / Arina Rahmat - Rahmat, Arina (2020)
The decentralisation in the construction industry has been determined by the lack of temporary multi-organisational (TMO) to collaborate successfully when delivering projects. There is incompetence of research in highlighting the importance of measuring the TMO integration and no evidence of the assessment model established for TMO integration in Malaysia. This research aims to establish an assessment model in measuring TMO integration for construction projects. In order to do so, five objectives have been expressed: (i) to identify the applicable and the most significant key determinants (KDs) of successful TMO integration, (ii) to establish an appropriate lead and lag of Quantitative Measures (QMs) for each KD, (iii) to determine an appropriate performance index of TMO integration in the range of five performance levels from poor to excellence performance, (iv) to develop an integrated model for measuring the TMO integration and (v) to verify and authenticate the utilisation of the assessment model in the real-life construction projects. In this study, a mixed method was used for data collection namely, semi-structured interview and Delphi questionnaire survey. Delphi questionnaire survey was carried out to obtain the information regarding the current practices of TMO integration by practitioners from vigorous segments of the Malaysian construction industry. The significant contributions of this research in the clarification of the KDs in TMO integration and introduced significant of KDs and the range of index to measure the performance index of KDs and QMs. The limitations of this research were limited to experience contractors that registered under Construction Industry Development Board (CIDB) and awarded in Malaysian Construction Industry Excellence Awards 2016 (MCIEA). This research contributes not only to expand the knowledge in the concept of collaboration and integration but also for the implementation of collaboration and integration in the construction industry, particularly in Malaysia, through the developed assessment. The upcoming research can replicate the theoretical models approaches to investigate the measuring of the new variables KDs.